Content analysis of witness testimony − between cognitive linguistics and forensic psychology - Liber, Katarzyna (Papers in Linguistics, 2019)
This article attempts to investigate the legitimacy of including the linguistic perspective to the content analysis of witness testimony, which at the present time is being primarily developed in the area of forensic psychology. If we consider that at least part of the nineteen CBCA criteria included in the Statement Validity Assessment method seems to be rather inaccurate and ineffective, it cannot be treated as a credible and objective tool to be applied in the Polish forensic practice. The article presents the former achievements of linguists in creating criteria for testimony content analysis and their definitions to possibly be applied in practice. It also presents the results of a diagnostic accuracy survey carried out on a Polish language material on the currently existing linguistic criteria and author’s new proposals.